The Role of Stress Granules in the Neuronal Differentiation of Stem Cells - Jeong, Sin-Gu; Ohn, Takbum; Jang, Chul Ho; Vijayakumar, Karthikeyan; Cho, Gwang-Won (Molecules and cells, 2020)
creativecommons.org/licenses/by-nc-sa/3.0/. Cells assemble stress granules (SGs) to protect their RNAs from exposure to harmful chemical reactions induced by environmental stress. These SGs release RNAs, which resume translation once the stress is relieved. During stem cell differentiation, gene expression is altered to allow cells to adopt various functional and morphological features necessary to differentiate. This process induces stress within a cell, and cells that cannot overcome this stress die. Here, we investigated the role of SGs in the progression of stem cell differentiation. SGs aggregated during the neuronal differentiation of human bone marrow-mesenchymal stem cells, and not in cell lines that could not undergo differentiation. SGs were observed between one and three hours post-induction; RNA translation was restrained at the same time. Immediately after disassembly of SGs, the expression of the neuronal marker neurofilament-M (NFM) gradually increased. Assembled SGs that persisted in cells were exposed to salubrinal, which inhibited the dephosphorylation of eukaryotic translation initiation factor 2 subunit 1 (eIF2α), and in eIF2α/S51D mutant cells. When eIF2α/S51A mutant cells differentiated, SGs were not assembled. In all experiments, the disruption of SGs was accompanied by delayed NF-M expression and the number of neuronally differentiated cells was decreased. Decreased differentiation was accompanied by decreased cell viability, indicating the necessity of SGs for preventing cell death during neuronal differentiation. Collectively, these results demonstrate the essential role of SGs during the neuronal differentiation of stem cells.